Serotonin blood level study, anxiety-depressive states indicators and patients life quality after laparoscopic treatment of gastroesophageal reflux disease - Haidarzhi, Ye. I.; Гайдаржі, Євген Іванович (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of the work was to study the dynamics of serotonin in the blood during laparoscopic total fundoplication and analyze the correlation of this hormone with the psychological well-being of patients before and after surgical treatment of GERD. Materials and methods. Laparoscopic fundoplication by Short Floppy Nissen modification was performed in 35 patients with GERD. There were 26 (74.3 %) women, 9 (25.7 %) men. Age – 55.3 ± 11.3. The comparison group consisted of 20 healthy volunteers (women – 14 (70.0 %); men – 6 (30.0 %), average age – 56.7 ± 10.6), who did not undergo surgery. The groups were comparable by gender and age. The studies were carried out in venous blood plasma, samples of which were maintained using standard methods and stored in a low-temperature freezer at a temperature of -80 °C. Tests for serotonin (Serotonin ELISA, RE59121, IBL) were studied on the immunoenzyme complex ImmunoChem-2100 (USA) of the Department of Clinical Laboratory Diagnostics in the Zaporizhzhia State Medical and Pharmaceutical University. The concentration of the last indicators was expressed in ng/ml. The presence of concomitant anxiety, depression and level of psychological well-being was assessed using the GAD-7, PHQ-9 and SF-36 questionnaires. Statistical assessment of the research results was carried out using the Statistica for Windows 13 software package (StatSoft Inc., No. JPZ804I382130ARCN10-J). Differences were considered statistically significant at p < 0.05. Results. The serotonin level in the blood of practically healthy people was 5.8 ± 1.5 ng/ml. In the main group serotonin values before surgical treatment were 3.1 ± 1.3 ng/ml. After surgical treatment the serotonin level increased to 5.4 ± 1.8 ng/ml and was not statistically different from the level of practically healthy patients. The dynamics of serotonin levels correspond to the dynamics of the patients number with signs of anxiety and depression before and after surgery in the main group, as well as the improvement in the psychological state of patients after surgery compared to preoperative data on the scales of the “psychological component” of SF-36 health questionnaire: Vitality (VT), Social Functioning (SF), Role-Emotional (RE), Mental Health (MH). Мета роботи – вивчити динаміку серотоніну в крові під час лапароскопічної тотальної фундоплікації та проаналізувати кореляцію цього гормона з психологічним самопочуттям пацієнтів до та після хірургічного лікування ГЕРХ. Матеріали та методи. Лапароскопічну фундоплікацію в модифікації Short Floppy Nissen виконано 35 пацієнтам із ГЕРХ: 26 (74,3 %) жінкам, 9 (25,7 %) чоловікам віком 55,3 ± 11,3 року. У групу порівняння залучили 20 здорових волонтерів (14 (70,0 %) жінок, 6 (30,0 %) чоловіків, середній вік – 56,7 ± 10,6 року), яким операцію не робили. Групи зіставні за статтю та віком обстежених. Здійснили дослідження в плазмі венозної крові, зразки якої одержали за стандартною методикою та зберігали у низькотемпературній морозильній камері при температурі -80 °C. Рівень серотоніну (Serotonin ELISA, RE59121, IBL) визначили, застосувавши імуноферментний комплекс ImmunoChem-2100 (США) на базі кафедри клінічної лабораторної діагностики Запорізького державного медико-фармацевтичного університету. Концентрація показників наведена у нг/мл. Наявність супутньої тривоги, депресії та рівня психологічного благополуччя оцінювали з використанням опитувальників GAD-7, PHQ-9 та SF-36. Статистично результати дослідження проаналізували, застосувавши програмний пакет Statistica for Windows 13 (StatSoft Inc., № JPZ804I382130ARCN10-J). Статистично значущими вважали відмінності при p < 0,05. Результати. Рівень серотоніну в крові практично здорових людей становив 5,8 ± 1,5 нг/мл. В основній групі до хірургічного лікування вміст серотоніну становив 3,1 ± 1,3 нг/мл. Після хірургічного лікування рівень серотоніну підвищився до 5,4 ± 1,8 нг/мл і статистично не відрізнявся від показника практично здорових пацієнтів. Динаміка рівня серотоніну відповідає динаміці кількості пацієнтів з ознаками тривоги та депресії до та після операції в основній групі, а також покращенню психологічного стану хворих після операції порівняно з доопераційними даними за шкалами «Психологічного компонента» здоров’я за опитувальником SF-36: життєва активність (Vitality – VT), соціальне функціонування (Social Functioning – SF), рольове функціонування, зумовлене емоційним станом (Role-Emotional – RE), психічне здоров’я (Mental Health – MH).
Вивчення рівня серотоніну крові, показників тривожно-депресивних станів і якості життя хворих після лапароскопічного лікування гастроезофагеальної рефлюксної хвороби
ORCID ID: 0000-0001-7211-1795
Keywords: gastroesophageal reflux disease; anxiety; depression; quality of life; serotonin; гастроезофагеальна рефлюксна хвороба; тривога; депресія; якість життя; серотонін